MOBILE APPLICATION FOR SKIN CARE PERSONALIZATION AT JASMINE BEAUTY CLINIC USING ANDROID - Shinta Bomi Bomi; Cindy Himawan (President University, 2019)
Jasmine Beauty Clinic is a beauty clinic that serves consultation on facial skin problems, maintain facial skin, facial treatments, and selling skin care products. Patients who want to have consultation, treatments, and buy skin care products must come to the clinic with limited time according to the schedule of the clinic. Patients are required to have a consultation with a dermatologist before getting treatment or buying products, but they have to wait long enough to get a consultation because of the large number of patients. Often some patients cannot have consultations because the dermatologist’s schedule is full. Based on this problem, an Android-based application is created to analyze the type of skin they have and get recommendation on which product and treatment combination they are supposed to use.